2015
DOI: 10.7205/milmed-d-14-00490
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of the U.S. Marine Corps Fitness Tests (2000–2012)

Abstract: This article describes the performance of active duty U.S. Marines on the Physical Fitness Test (PFT) and Combat Fitness Test (CFT) during calendar years 2000 through 2012. Our study sample included PFT composite scores (n = 543,185), PFT and CFT composite scores (n = 160,936), and PFT and CFT event scores (n = 135,926 and n = 201,953, respectively). In general, all Marines performed very well on each fitness test, with overall annual improvements. Interestingly, the majority of female Marines passed the minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…As professional warrior-athletes, every Marine must be physically fit regardless of age, grade, gender or duty assignment (24,25,26,27). Though current USMC PFT and CFT testing parameters are different from when previous studies or articles were written (3,8,13,14,16,30,33,37), information reported previously is useful in understanding why such modifications were made to the PFT and CFT protocols. While the aforementioned studies (3,13) begin the conversation about the USMC PFT and CFT relationship they did not explore correlation data between PFT and CFT events or total scores.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…As professional warrior-athletes, every Marine must be physically fit regardless of age, grade, gender or duty assignment (24,25,26,27). Though current USMC PFT and CFT testing parameters are different from when previous studies or articles were written (3,8,13,14,16,30,33,37), information reported previously is useful in understanding why such modifications were made to the PFT and CFT protocols. While the aforementioned studies (3,13) begin the conversation about the USMC PFT and CFT relationship they did not explore correlation data between PFT and CFT events or total scores.…”
Section: Introductionmentioning
confidence: 94%
“…The USMC implemented the Combat Fitness Test (CFT) in 2008 and began official scoring in the fall of 2009 (3). The CFT is a complement to the PFT and measures additional functional elements of general fitness to include agility, coordination and anaerobic capacity (26).…”
Section: Introductionmentioning
confidence: 99%
“…Our pelvic ring fracture incidence of 0.35 per 1,000 person-years (95% CI, 0.34-0.36) lies in between previously reported incidence rates. However, the U.S. military population of young, active, predominantly male individuals contrasts with the typical adult population that may have lesser physical and functional demands [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Juntos, todos estos parámetros, a través de ecuaciones estandarizadas y validadas en varias poblaciones, 10 proporcionan un sistema dimensional que permite representar gráficamente la condición física del sujeto o una muestra con respecto a un estándar, pero también con respecto a sí mismo en otro momento. El somatotipo se ha utilizado ampliamente para la evaluación global de la condición física, para compararlo con una condición ideal y para evaluar la composición corporal relacionada con la salud, [11][12][13][14][15] así como los resultados de los programas deportivos y el acondicionamiento físico. [16][17][18] Hasta ahora, los métodos de evaluación de la condición física en el medio militar consistían de forma predominante en pruebas prácticas con series de ejercicios, orientadas hacia la evaluación de la capacidad aeróbica, además de la fuerza muscular, como pruebas de longitud, abdominales, flexiones y estiramientos, lagartijas y carrera de obstáculos.…”
Section: Wwwmedigraphicorgmxunclassified